An Information Sharing System for Multi-Professional Collaboration in the community-based integrated healthcare system - Hideaki Kanai; Akinori Kumazawa (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2021)
Currently, Japan is rapidly aging. Japanese government agencies report that the percentage of elderly people whose ages are at least 65 years will increase by up to about 30 percent in 2025. As one of the measures towards this situation, the community-based integrated healthcare system will be introduced in Japan. The system aims to provide elderly people living at home with appropriate health, medical, and welfare services. We focus on the burden of sharing information on the situation of the elderly at home among health, medical, welfare staffs, and neighbors. We have been developing a supporting system for sharing information on the situation of the elderly at home and conducted a field test around one year. We consider that various stakeholders involved in the community comprehensive health care system could recognize the importance of information sharing and collaboration with them through this kind of social implementation